Effect of propylene glycol on in vitro LPS activation of rat peritoneal macrophage - SAINI, M; GUPTA, L K; MALIK, S V S; SHARMA, BHASKAR (The Indian Journal of Animal Sciences, 2014)
Propylene glycol (PG), a relatively nontoxic industrial solvent and a common feed additive for cows, decreased the phagocytic index of Listeria monocytogenes significantly (P<0.05) by rat peritoneal macrophages after in vitro activation at a concentration as low as 20 ug/ml. This reduction was concentration dependent in the range of 5 to 50 ug/ml. Lipopolysachharide (LPS) activation of the macrophages in vitro enhanced the phagocytic index of L. monocytogelles in a concentration-dependent manner. Significant (P<0.05) increase was observed with 10 ug LPS/ml. When LPS activated macrophages were simultaneously treated with 5-50 ug propylene glycol/ml, the phagocytic index of the treated cells remained similar to that of control. It is concluded that propylene glycol is inhibiting the LPS activation of rat peritoneal macrophages and thereby suppressing the non-specific immune response.